2020
DOI: 10.1021/acs.organomet.0c00459
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Ammonia Borane Dehydrogenation: Mechanistic Insight and Isolation of a Cobalt Hydride-Amidoborane Complex

Abstract: A Co(I) complex featuring the electron-rich monoanionic bis(carbene) aryl pincer ligand ( Mes CCC) ( Mes CCC = bis(2,4,6-trimethylphenyl-benzimidazol-2-ylidene)phenyl), ( Mes CCC)Co-py (1), was found to catalytically dehydrogenate ammonia borane (NH 3 BH 3 , AB) in THF at 60°C. This process releases 1.7 ± 0.1 equiv of H 2 per AB with simultaneous formation of both soluble (borazine and polyborazylene) and insoluble (poly(aminoborane)) BN-containing species. To help elucidate the Co species present under the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 69 publications
0
21
0
1
Order By: Relevance
“…Ammmonia–borane (NH 3 BH 3 , AB) dehydrogenation may represent a proof-of-concept target for bifunctional activation by means of heterometallic complexes. Indeed, AB contains both hydridic (B–H) and protic (N–H) hydrogens, which could be activated by interaction with the Lewis acid site and the Lewis base site, respectively, of a heterometallic metal-only Lewis pair . AB dehydrogenation is a very interesting reaction for the potential application of AB as hydrogen storage medium for transportation. Several monometallic transition metal complexes have been investigated as catalysts for AB dehydrogenation, including NHC complexes and the use of noninnocent ligands and homometallic carbonyls. Bifunctional AB dehydrogenation may be promoted by [L n M]–H transition metal hydrides, where the [L n M] fragment acts as Lewis acid and the hydride holds a negative charge (Lewis base).…”
Section: Introductionmentioning
confidence: 99%
“…Ammmonia–borane (NH 3 BH 3 , AB) dehydrogenation may represent a proof-of-concept target for bifunctional activation by means of heterometallic complexes. Indeed, AB contains both hydridic (B–H) and protic (N–H) hydrogens, which could be activated by interaction with the Lewis acid site and the Lewis base site, respectively, of a heterometallic metal-only Lewis pair . AB dehydrogenation is a very interesting reaction for the potential application of AB as hydrogen storage medium for transportation. Several monometallic transition metal complexes have been investigated as catalysts for AB dehydrogenation, including NHC complexes and the use of noninnocent ligands and homometallic carbonyls. Bifunctional AB dehydrogenation may be promoted by [L n M]–H transition metal hydrides, where the [L n M] fragment acts as Lewis acid and the hydride holds a negative charge (Lewis base).…”
Section: Introductionmentioning
confidence: 99%
“…20−22 Although direct activation of amines by borohydride complexes has been reported only rarely, Fout et al recently achieved the activation of a N−H bond in H 3 N• BH 3 by the cobalt(I) complex (MesCCC)Co-py, affording a first example of a hydride-amidoborane complex on a late transition metal. 23 Very recently, we demonstrated dehydrogenation-regeneration of iron amido-borane complex Cp*Fe-(η 1 -H 3 B-NHC 6 H 4 PPh 2 ), which was synthesized from an iron tetraborohydride precursor Cp*Fe(η 2 -BH 4 )(NCMe) with a phosphinoamine ligand 1,2-Ph 2 PC 6 H 4 NH 2 . 24 We report here the synthesis of cobalt arylborohydride complexes Cp*Co(κ 3 -…”
Section: ■ Introductionmentioning
confidence: 99%
“…Buil et al found the tetrahydridoborate osmium hydride, OsH­(η 2 -H 2 BH 2 )­(CO)­(P i Pr 3 ) 2 , is able to activate aryl amines, affording the amino-boryl complex by release of 4 equiv of H 2 (Figure , b) . Such an elementary reaction is promising because it is relevant to catalytic amine-borane dehydrogenation and related transfer hydrogenation reactions. Although direct activation of amines by borohydride complexes has been reported only rarely, Fout et al recently achieved the activation of a N–H bond in H 3 N·BH 3 by the cobalt­(I) complex (MesCCC)­Co-py, affording a first example of a hydride-amidoborane complex on a late transition metal . Very recently, we demonstrated dehydrogenation-regeneration of iron amido-borane complex Cp*Fe­(η 1 -H 3 B-NHC 6 H 4 PPh 2 ), which was synthesized from an iron tetraborohydride precursor Cp*Fe­(η 2 -BH 4 )­(NCMe) with a phosphinoamine ligand 1,2-Ph 2 PC 6 H 4 NH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of relevance to H 2 storage 1-10 and hydrogenation catalysis, [11][12][13][14][15] metal amine-borane complexes [16][17][18] and their dehydrogenated forms, such as amino-boranes [20][21][22] and iminoboranes 4 are arising as a signicant family in organometallic chemistry. In transition metal-catalyzed dehydrocoupling of amine-boranes and related transfer hydrogenations, the interactions between the metal and the borane fragment are essential to dehydrogenation and the consequent transformations.…”
mentioning
confidence: 99%
“…In transition metal-catalyzed dehydrocoupling of amine-boranes and related transfer hydrogenations, the interactions between the metal and the borane fragment are essential to dehydrogenation and the consequent transformations. [16][17][18][19][20] Specically, amino-borane complexes containing a M-H 2 B]NR 2 moiety are the primary dehydrogenated species and are oen identied as a resting point in the catalysis (Scheme 1a). [20][21][22] Management of reversible dehydrogenation-regeneration reactions on a M-BH 2 ]NR 2 platform could provide a strategy with which to design efficient catalysts capable of operating sustainable syntheses.…”
mentioning
confidence: 99%